Sex-specific differences and survival in patients with idiopathic pulmonary arterial hypertension 2008–2016. Issue 3 (12th August 2019) - Kjellström, Barbro; Nisell, Magnus; Kylhammar, David; Bartfay, Sven-Erik; Ivarsson, Bodil; Rådegran, Göran; Hjalmarsson, Clara
Background: Women with idiopathic pulmonary arterial hypertension (IPAH) have been found to have a worse haemodynamic status at diagnosis, but better survival than men. Over the past decade, demographics have changed and new treatments have become available. The objective of this study was to investigate sex differences in an incident IPAH population diagnosed between 2008 and 2016. Methods: Differences in clinical characteristics of patients included in the Swedish Pulmonary Arterial Hypertension Register (SPAHR) were analysed at the time of diagnosis. Survival by sex was investigated using Cox proportional hazard regression and Kaplan–Meier curves. Results: The study included 271 patients diagnosed with IPAH, median age was 68 (1st–3rd quartiles 54–74) years and 56% were women. At diagnosis, women were younger, had lower pulmonary vascular resistance and fewer comorbidities and more often received a combination of PAH-targeted therapies than men. Men had worse survival rates than women (hazard ratio 1.49; CI 1.02–2.18; p=0.038), but this difference did not remain after adjustment for age (hazard ratio 1.30; CI 0.89–1.90; p=0.178). Conclusions: Men with incident IPAH have worse crude survival than women. This is due to women being younger with a less pronounced comorbidity burden than men at the time of diagnosis. Despite minor differences in baseline characteristics between men and women, survival among patients with incident IPAH diagnosed 2008–2016 does not appear to be related to sex http://bit.ly/2JFgXhd